Nexus between Selected Macro Economic Variables and Stock Market Performance in Sri Lanka During (2017-2022): An Econometric Analysis - Induja, Y.; Vijayakumar, S. (Journal of Accounting and Finance, 2024)
Stock market contributes to the economic growth of the country in various ways. In other words, efficient allocation of domestic resources among developing sectors is seen as one of the main roles played by stock markets in the development process. Focusing on examining the relationship between stock market performance and macro-economic variables in Sri Lanka. Money supply, exchange rate, index of industrial production and interest rate used as independent variables and all share price index as dependent variable. It has been carried out with a focus on monthly time series data from January 2017 to December 2022. Eview includes the econometric procedures of augmented dickey fuller unit root test, heteroscedasticity test, serial correlation LM test, omitted variable test, stability diagnostic test, normality test, auto regressive distributed lag model bound test used to test the long run relationship between the variables and error correction model used to test the short run relationship between the variables. The test is revealed that there is positive and significant impact of money supply, exchange rate and index of industrial production on stock market performance while interest rate has negative significant impact on stock market performance in the long run. Further, it is found that there is a negative and significant impact of money supply on stock market performance while exchange rate has a significant positive impact on stock market perfor-mance in the short run. Interest rate does not significant impact on stock mar-ket performance in the short run. In order to attract stock market investments, the government should take measures such as maintaining stable stock prices, maintaining political and economic stability and developing market facilities and infrastructure facilities. Advances in block chain technologies will open up new avenues for modern stock market transactions.
Keywords: Stock market performance; Money supply; Exchange rate; Interest rate; Index of industrial production